2022
DOI: 10.3390/ijerph191811822
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Coping Style on the Relationship between Stress and Psychological Well-Being in Hong Kong Nursing Students

Abstract: Aims and objectives: To examine whether coping styles moderate the influence of stressors and psychological well-being in Hong Kong nursing students. Background: Stress could contribute to psychological distress in nursing students. Coping strategies are essential to mitigate psychological distress. So far, the moderating effects of coping between stressors and psychological well-being has not been thoroughly investigated. Design: This is a cross-sectional study conducted at four higher education institutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…We observed that greater engagement in emotion-focused coping buffered the effect of COVID-19 perseverative cognition on depression. Our result echoes with the literature indicating emotion-focused coping as a moderator in the relationship between heightened stress and negative mental health outcomes ( Austenfeld and Stanton, 2004 ; Cheng et al, 2022 ; Lin et al, 2010 ). This is also consistent with recent studies which found that positive reappraisal, a key component of emotion-focused coping, represented a protective factor against development of psychological distress during COVID-19 ( Ke et al, 2022 ; Riepenhausen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…We observed that greater engagement in emotion-focused coping buffered the effect of COVID-19 perseverative cognition on depression. Our result echoes with the literature indicating emotion-focused coping as a moderator in the relationship between heightened stress and negative mental health outcomes ( Austenfeld and Stanton, 2004 ; Cheng et al, 2022 ; Lin et al, 2010 ). This is also consistent with recent studies which found that positive reappraisal, a key component of emotion-focused coping, represented a protective factor against development of psychological distress during COVID-19 ( Ke et al, 2022 ; Riepenhausen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Dentro de los estudiantes universitarios se denota que los que estudian carreras orientadas al área de la salud muestran niveles de estrés mayores a los que exhiben los estudiantes que estudian otras carreras; ejemplo de ello son los diversos estudios en población universitaria en carreras como enfermería o medicina (Cheng et al, 2022;Lui et al, 2022;Ma et al, 2022;Pozos-Radillo et al, 2021;Priyadharshini et al, 2021;Rodríguez-Fernández et al, 2020;Valdez et al, 2022).…”
Section: Estrés En Estudiantes Del áRea De La Saludunclassified
“…Ineffective coping with stress may lead to psychological distress ( Li et al, 2009 ; Collin et al, 2020 ), which is commonly associated with depression, anxiety, and social dysfunction. In a cross-sectional study, Cheng et al (2022) reported that seeking support, problem-solving, and venting were the most common coping types used by the final year nursing students in Hong Kong; those nursing students who tended to use such coping strategies reported less psychological distress. Hence, assessment of various determinants of stress and distress is essential to suggest suitable remedial measures for stress mitigation.…”
Section: Introductionmentioning
confidence: 99%